2019
DOI: 10.1097/sla.0000000000003660
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Factors Impact Time to Surgical Recurrence After Ileocolectomy for Crohn's Disease

Abstract: Objective:The aim of this study was to evaluate factors associated with time to surgical recurrence after Crohn's ileocolectomy.Summary Background Data:The most common surgery performed for Crohn's disease is ileocolectomy. Identifying patients at high risk for surgical recurrence may assist with medical and surgical decision-making.Methods:Data were obtained from 409 patients with Crohn's disease (CD) who had undergone ≥1 ileocolectomies at Penn State Hershey Medical Center. Six single-nucleotide polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These include identifying patients at risk for earlier recurrence of Crohn's disease after ileocecectomy or correlating allele variants with a more severe overall course, including surgical complications. 37,50 Decades ago, such studies required complicated and expensive methods of investigation, but newer techniques of specimen study, such as next-generation sequencing, RNA sequencing, rapid 16S microbiome analysis, and bioinformatic processing, have led to a deluge of candidate biomarkers that can potentially assist the surgeon in clinical assessment and care of the surgical patient. As assay platforms have become more affordable and easier to use, whole genome and exome sequencing can be readily performed, as is evidenced by these platforms now being commercially available to the lay public for relatively low prices.…”
Section: Biobank and Surgical Geneticsmentioning
confidence: 99%
“…These include identifying patients at risk for earlier recurrence of Crohn's disease after ileocecectomy or correlating allele variants with a more severe overall course, including surgical complications. 37,50 Decades ago, such studies required complicated and expensive methods of investigation, but newer techniques of specimen study, such as next-generation sequencing, RNA sequencing, rapid 16S microbiome analysis, and bioinformatic processing, have led to a deluge of candidate biomarkers that can potentially assist the surgeon in clinical assessment and care of the surgical patient. As assay platforms have become more affordable and easier to use, whole genome and exome sequencing can be readily performed, as is evidenced by these platforms now being commercially available to the lay public for relatively low prices.…”
Section: Biobank and Surgical Geneticsmentioning
confidence: 99%
“…While its role in CD pathogenesis is certain, its implication in recurrence, although reason-able, is less definite and a meta-analysis [17] has failed to demonstrate a significant association [18]. A more recent study has identified instead, at multivariable analysis, an independent association between recurrence and a particular NOD2 polymorphism, rs2066844, which was not previously investigated [19]. Another gene, SMAD3, has never been linked to CD pathogenesis but was found to be an independent predictor of recurrence after ileocolic resection [20].…”
Section: Derangements In the Pattern Recognition Receptor Andmentioning
confidence: 99%
“…Several studies have assessed the risk factors for postoperative CD recurrence. Reported risk factors for postoperative recurrence include a smoking habit, family history, young age at diagnosis, ileocolonic disease, perianal disease, preoperative duration and perforating lesions[ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%